The Canadian way of counterterrorism: introducing the GATE-Canada data set. Issue 3 (1st September 2016) - Chenoweth, Erica; Dugan, Laura
Abstract: How does Canada fight terrorism, and to what effect? In this article, we introduce an original data set of all reported actions taken by the Canadian government in relation to both domestic and international terror groups between 1985 and 2013. Data include conciliatory and repressive, verbal and physical, and discriminate and indiscriminate actions relating to a wide variety of constituencies. We demonstrate the value of these data by applying them to a key scholarly and policy question: whether actions by Canada relevant to terrorism abroad affect its terrorism relevant actions at home. Our results suggest that international actions related to terrorism did lead to a subsequent increase in domestic actions. Interestingly, the effects of international actions on domestic actions after 9/11 extend not only to Muslims in Canada, but also to other Canadian political constituencies. This finding lends support to the hypothesis that an increased mandate and resources to counter a particular threat may lead to more generalized counter-terrorism initiatives domestically.